The burdens of lung cancer involved multiple primary cancers and its occurring patterns–SEER Analysis between 1973 and 2006 - Rui Mao (Nature Portfolio, 2017)
Abstract The prognosis of malignancies has improved in recent years, subsequent primary cancers (SPCs) have become more frequent. This study investigates the patterns of lung cancer involved multiple primary cancers. We enrolled 206,619 primary lung cancer patients and 2,071,922 patients with other primary malignancies from Surveillance, Epidemiology and End Results (SEER) database. Observed annual risk (OAR) and absolute numbers were used to describe the risk of SPC and observed cases of SPC per 10,000 person-years at risk. Overall, OAR of SPCs following lung cancer was 176.28. At follow-up, 41.26% of SPCs occurred within 12–59 months while the highest OAR appeared after 120 months. The overall OAR of subsequent lung cancer after other malignancies was 27.90. Overall, the highest OAR and the highest absolute numbers of subsequent lung cancers were noticed 60–119 months and over 120 months post-diagnosis, respectively. Ten related cancers were listed. Our findings encourage surveillance for 10 common SPCs in lung cancer survivors during follow-up as well as screening for lung cancer after 10 common malignancies.